Syirik dan Dampaknya Bagi Kehidupan Manusia - Sitha Nurcahaya Dewi; Jelita Pinasti; Dwi Rahmadani; Muhammad Aldi Rahman; Wismanto Wismanto (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Shirk is the act or belief of associating Allah SWTwith something or someone in worship or his attributes. In Islam, shirk is considered a major sin that has negative consequences for humans. Allah SWTsays: "Verily, Allah SWTwill not forgive the sin of shirk, and He forgives all sins other than that, for whom he wills. Whoever associates partners with Allah, then indeed he has committed a great sin" (QS. an-Nisa [4] verse 48). This article aims to discuss the definition of shirk, the classification of shirk, and its effects on individuals and society. The research is conducted using a literature study method that incorporates various sources such as the Qur'an, authentic traditions, and the works of scholars on this theme. The results show that the consequences of shirk include damage to the relationship with Allah, canceling acts of worship, being trapped in hypocrisy, and causing uncertainty in one's beliefs.